Construction of Cell–Extracellular Matrix Microenvironments by Conjugating ECM Proteins on Supported Lipid Bilayers - Huang, Chun-Jen; Chang, Ying-Chih (Frontiers in Materials, 2019)
The cell membrane is an organized and fluid structure that modulates cellular activities in response to specific extracellular signals, and maintains the critical communication, integration and homeostasis between the cytosol and the extracellular matrix (ECM). In recent years, tissue engineering and cell biology research has been rapidly progressed by a remarkable understanding of cell and ECM interfaces. In this review, the design of new biomimetic platforms based on the conjugation of ECM proteins on solid supported lipid bilayers (SLBs) will be summarized. The platforms provide a better system to evaluate cellular responses to specific recognition events, gradient, mechanical property, nanostructures, and inter- and intra-molecular interactions of ECM proteins on a nonfouling and fluid membrane. Moreover, the findings from the molecular interactions and cellular activities will be highlighted to look into the cell-materials mechanisms.